Minimally processed crude leaf extracts of Nicotiana benthamiana containing recombinant foot and mouth disease virus-like particles are immunogenic in mice - Ruiz, Vanesa (2018)
Foot-and-mouth disease (FMD) remains one of the most feared viral diseases affecting cloven-hoofed animals, and results in severe economic losses. Currently available vaccines are based on inactivated FMD virus (FMDV). The use of recombinant FMDV-like particles (VLPs) as subunit vaccines has gained importance because of their immunogenic properties and safety. We evaluated the production of FMD VLPs, via Agrobacterium-mediated transient expression, and the immunogenicity of these structures in mice. Leaves were infiltrated with pEAQ-HT and pRIC 3.0 vectors encoding the capsid precursor P1-2A and the protease 3C. The recombinant protein yield was 3–4 mg/kg of fresh leaf tissue. Both groups of mice immunized with purified VLPs and mice immunized with the crude leaf extract elicited a specific humoral response with similar antibody titers. Thus, minimally processed plant material containing transiently expressed FMD VLPs could be a scalable and cost-effective technology for the production of a recombinant subunit vaccine against FMDV.